Predator interference and stability of predator-prey dynamics - Přibylová, Lenka; Berec, Luděk (Journal of mathematical biology, 2015)
Predator interference, that is, a decline in the per predator consumption rate as predator density increases, is generally thought to promote predator-prey stability. Indeed, this has been demonstrated in many theoretical studies on predator-prey dynamics. In virtually all of these studies, the stabilization role is demonstrated as a weakening of the paradox of enrichment. With predator interference, stable limit cycles that appear as a result of environmental enrichment occur for higher values of the environmental carrying capacity of prey, and even a complete absence of the limit cycles can happen. Here we study predator-prey dynamics using the Rosenzweig-MacArthur-like model in which the Holling type II functional response has been replaced by a predator-dependent family which generalizes many of the commonly used descriptions of predator interference. By means of a bifurcation analysis we show that sufficiently strong predator interference may bring about another stabilizing mechanism. In particular, hysteresis combined with (dis)appearance of stable limit cycles imply abrupt increases in both the prey and predator densities and enhanced persistence and resilience of the predator-prey system. We encourage refitting the previously collected data on predator consumption rates as well as for conducting further predation experiments to see what functional response from the explored family is the most appropriate.
Keywords: biologické modely; Models, Biological; Mathematical Concepts; zvířata; Population Dynamics; ekosystém; Computational Biology; populační dynamika; Ecosystem; matematické pojmy; potravní řetězec; výpočetní biologie; Food Chain; Animals